Customer Waiting Time in Department of Labour, Kuala Terengganu: A Queuing Approach / Norsyafiqah Mohamad, Masnita Misiran and Zahayu Md Yusof - Mohamad, Norsyafiqah; Misiran, Masnita; Md Yusof, Zahayu (Universiti Teknologi MARA, Negeri Sembilan, 2020)
Businesses adopt queuing mechanism as it can improve efficiency and provide economic use of resources. Some business segment that normally adapted queuing theory include assessing staff scheduling, productivity, performance, and customers waiting time. This article will adopt queuing theory to current service provided by Department of Labour, Kuala Terengganu. As the department is committed to provide quality services to its customer, the level of satisfaction and current queueing time need to be investigated. To achieve this, four elements in queueing theory - arrival rate, the queuing discipline, the service and also the cost structure are utilized. Arrival rate is measured as way in which customer arrives at this department and entered for receiving a service. Single server queuing model is known as infinite queue length model (exponential service) was used in this study. This model is based on certain assumptions about queuing, as the arrivals are described by Poisson probability distribution and arrive from infinite population. This study has demonstrated that, majority of the customers are dissatisfied with services offered and the major cause of dissatisfaction is the long waiting time. Sunday shows the busiest day at Department of Labour, Kuala Terengganu when there are too many customers and duty officer faced a hectic day on Sunday, followed by Thursday and Wednesday. Department of Labour, Kuala Terengganu needed to do the other internal procedures for reducing waiting times and thus ensuring an effective services system. This study recommended of adding a new checkout counter and hiring another employee to help duty officer improve the operation at Department of Labour, Kuala Terengganu.